The Analysis of Risk Factors Affecting the Proportion of Standard Threshold Shift among Manufacturing Workers - Ratsmita, Firly; Ilyas, Muhammad; Jen Fuk, Liem; S. Soemarko, Dewi; Chandra, Levina (UI Scholars Hub, 2023)
Introduction. About 82% of cases of hearing loss due to employment occur in workers in the manufacturing sector. The prevalence of hearing loss has a permanent impact that can be detected by standard threshold shift (STS). The aim of the study was to determine the relationship between individual and occupational risk factors on the proportion of STS. Methods. The research was a cross-sectional study on employees with noise exposure. The independent variables include individual factors such as age, history of hypertension, history of diabetes mellitus, smoking, body mass index, and occupational factors such as the history of chemical exposures, working period, provision of personal protective equipment (PPE), and working area. Results. The study showed that the associated risk factors were working period (OR 1.9; 95% CI 1.0-3.4), history of diabetes mellitus (OR 17; 95% CI 2.1 -146), and obesity (OR 2.4; 95% CI 1.1-5.0). The variable of history of diabetes mellitus, working period, and BMI accounted for about 12% of the proportion of STS with the main predictive value being the history of diabetes mellitus in multivariate analysis. Conclusion. The proportion of STS in the manufacturing company in the period 2018 to 2020 was 33.5%. The high proportion of STS employees may indicate the need to evaluate the hearing protection program that has been running since 2016. Suggestions for the company including improving employee protection programs, monitoring and evaluating ongoing hearing protection programs, and health programs, especially chronic diseases such as diabetes mellitus and weight loss. .